2015
DOI: 10.1186/s12936-015-1000-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and frequency of G119S mutation in ace-1 gene within Anopheles sinensis populations from Guangxi, China

Abstract: BackgroundMalaria is one of the most serious vector-borne diseases in the world. Vector control is an important measure for malaria prevention and elimination. However, this strategy is under threat as disease vectors are developing resistance to insecticides. Therefore, it is important to monitor mechanisms responsible for insecticide resistance. In this study, the presence of G119S mutation in the acetyl cholinesterase-encoding gene (ace-1) was investigated in nine Anopheles sinensis populations sampled acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…The genomic DNA of individual adult mosquitoes was prepared as described elsewhere [ 28 , 29 ]. A fragment containing codon 1014 of AS - VGSC gene was amplified using primers kdr-F (5′-TGCCACTCCGTGTGTTTAGA-3′) and kdr -R (5′-GAGCGATGATGATCCGAAAT-3′) [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The genomic DNA of individual adult mosquitoes was prepared as described elsewhere [ 28 , 29 ]. A fragment containing codon 1014 of AS - VGSC gene was amplified using primers kdr-F (5′-TGCCACTCCGTGTGTTTAGA-3′) and kdr -R (5′-GAGCGATGATGATCCGAAAT-3′) [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Genotyping of codon 119 of An. sinensis ace-1 gene was done by PCR-RFLP [12]. The frequency of the G119S mutation in each collection was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Recent surveys have revealed that the G119S occurs at high frequencies in many field populations of An. sinensis in Asia [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…The genomic DNA of individual adult mosquitoes was prepared as described elsewhere [ 11 , 28 ]. A fragment of exon 7 encoding the M2 transmembrane domain region was amplified using primers ASRdl-7F (AGTTTGTACGTTCGATGGGTTA) and ASRdl-7R (CCAGCAGACTGGCAAATACC).…”
Section: Methodsmentioning
confidence: 99%
“…Although the distribution and frequency of insecticide resistance-conferring mutations in the acetylcholinesterase and voltage gated sodium channel were determined in An. sinensis collected extensively across Guangxi in previous studies [ 11 , 12 ], other questions related to insecticide resistance remain to be answered.…”
Section: Introductionmentioning
confidence: 99%